2020
DOI: 10.1371/journal.pone.0239378
|View full text |Cite|
|
Sign up to set email alerts
|

The path to international medals: A supervised machine learning approach to explore the impact of coach-led sport-specific and non-specific practice

Abstract: Research investigating the nature and scope of developmental participation patterns leading to international senior-level success is mainly explorative up to date. One of the criticisms of earlier research was its typical multiple testing for many individual participation variables using bivariate, linear analyses. Here, we applied state-of-the-art supervised machine learning to investigate potential non-linear and multivariate effects of coach-led practice in the athlete's respective main sport and in other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The findings were robust across different types of sports and were also consistent with results from original studies that involved control for potential confounds through matched-pairs design, multi-year longitudinal quasi-experiments, and multivariate linear and non-linear analyses [ 24 , 25 , 27 , 28 , 46 – 48 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings were robust across different types of sports and were also consistent with results from original studies that involved control for potential confounds through matched-pairs design, multi-year longitudinal quasi-experiments, and multivariate linear and non-linear analyses [ 24 , 25 , 27 , 28 , 46 – 48 ].…”
Section: Discussionsupporting
confidence: 82%
“…Among empirical studies examining predictors of sports performance, an analysis of the samples revealed wide ranges of age categories (juniors, seniors), types of sports, and performance levels (local to Olympic competition level). Furthermore, past studies typically analysed effects of predictor variables separately and did not consider potential associations between effects of different predictors, with a few exceptions [24][25][26][27][28].…”
Section: Key Pointsmentioning
confidence: 99%
“…Specifically considering participation in FAL activities, HS male participants were involved in more activities compared to their LS counterparts. These findings are consistent with the theoretical tenets of the DMSP 18 and numerous retrospective studies on team sports that empirically evidenced that elite players engage extensively in various sports, before specializing in the main sport 1,25,[46][47][48] . The findings also support the theoretical proposal of Côté and colleagues 16,18 suggesting that early diversification does not hinder elite sport participation in sports where peak performance is reached after maturation, as observed in the majority of team sports.…”
Section: Discussionsupporting
confidence: 86%
“…14 In fact, much of the existing literature indicates that early sport specialization is not a predictor of success and may even impede long-term achievement in some sports. [2][3][4]7,15,16,18,20,22,27,28,37 For some young athletes, the youth sport experience involves nearly continuous year-round participation in a single sport, frequent travel, and regular competitive events that can feature a number of games played over a short period of time, all in addition to the demands of academic work and family and community commitments. This may leave youth athletes with limited time for rest or peer socialization outside of sport and may also negatively affect nutrition and sleep.…”
mentioning
confidence: 99%
“…14 In fact, much of the existing literature indicates that early sport specialization is not a predictor of success and may even impede long-term achievement in some sports. 2 - 4 , 7 , 15 , 16 , 18 , 20 , 22 , 27 , 28 , 37 …”
mentioning
confidence: 99%